Flexural Behavior of Reinforced Concrete Beams with Steel-Plate Reinforced Vertical Opening - Abed Shnait, Masharq; Izzet, Amer F. (Salehan Institute of Higher Education, 2024)
The structural response of simply supported Reinforced Concrete (RC) beams with square vertical openings is investigated in this work. Studies were conducted using seven specimens of RC beams, with the aim of comparing beams with vertical openings to those without. Meanwhile, the other beams featured carefully positioned square openings. Note that one of these beams served as the control and had no openings. Each beam was the same length (1400 mm) with a 180×120 mm cross-section. Two-point loads were applied over a span of 1200 mm throughout the testing method, with a central load placed 300 mm from the ends. The openings were positioned in the middle of the span and came in three different widths: 20, 40, and 60 mm. Openings were made using either 1.5 mm thick square steel tubing or none at all. The major goal of this study was to determine whether the steel tube could compensate for the decrease in beam strength and the impact of decreasing beam cross-section (producing opening). Correspondingly, the beam ultimate load was found to decrease by 15.75%, 24.2%, and 32.5% for opening widths of 20 mm, 40 mm, and 60 mm, respectively, as the opening width increased. On the other hand, the performance gain for beams strengthened with steel plates when steel tubes were used was 11.78%, 12.14%, and 13.28% for the respective opening widths. Doi: 10.28991/CEJ-2024-010-09-04 Full Text: PDF